Wildlife, loggers and livelihoods in the Congo Basin - Sayer, Jeffrey A.; Ndikumagenge, C.; Campbell, Bruce M.; Usongo, L. (Earthscan, 2005)
This paper examines the history of forest management and conservation in the Congo Basin. It identifies some of the reasons for the limited success in applying ecosystem approaches to forest management. The lack of long-term consistent policies and programmes and the relative weakness of forest sector institutions emerge as fundamental problems. The chapter identifies one tool, participatory modelling, that can help stakeholders to get grips with the complecity of the social-ecological systems of which their forests are part. Such modelling exercises can help enable stakeholders with diverse interests to explore scenarios and negotiations outcomes that are consistent with ecosystem approaches to sustainable forest management.